Grafting macromolecular chains on the surface of graphene oxide through crosslinker for antistatic and thermally stable polyethylene terephthalate nanocomposites. Issue 51 (22nd November 2022) - Meng, Zhaorui; Lu, Shichao; Zhang, Dianbo; Liu, Qun; Chen, Xiangdong; Liu, Wei; Guo, Cheng; Liu, Zongfa; Zhong, Weihua; Ke, Yangchuan
Abstract : The graphene oxide (GO) and polyethylene terephthalate (PET) molecular chains are connected together by the two amino groups of the crosslinking agent p -phenylenediamine (PPD). Abstract : The graphene oxide (GO) and polyethylene terephthalate (PET) molecular chains are connected together by the two amino groups of the crosslinking agent p -phenylenediamine (PPD). The presence of macromolecular chains could make GO uniformly dispersed in the polymer matrix, improving the antistatic performance and thermal stability of the nanocomposite. In this paper, GO was prepared by the improved Hummers, method. In the first step, an amine group of PPD undergoes a nucleophilic ring-opening reaction with an epoxy group on GO. Multiple characterization methods indicate that PPD is successfully grafted to the surface of GO sheets and GO is partially reduced simultaneously. The graphene layer spacing increased from 0.81 nm for GO to 1.49 nm for grafted graphene oxide (g-GO). The number of oxygen-containing functional groups in GO is also reduced. The conductivity of g-GO at room temperature is 1.8 S cm −1, which is much higher than that of GO. In addition, the thermal stability of g-GO has also been improved. In the second step, the other unreacted terminal amino group of PPD is grafted to PET molecular chains through hydrogen bonding or amidation reactions. Antistatic and thermally stable nanocomposites were then obtained by hot pressing. Different ratios of graphene/polyester nanocomposites were obtained. At the same time, the g-GO is further thermally reduced. The thermal stability of PET/g-GO nanocomposite has been greatly improved, while the thermal stability of PET/GO nanocomposite is basically the same as that of pure PET. For the PET/g-GO nanocomposite, the residue rate has increased by nearly 10%, and the maximum thermal decomposition temperature has also increased by 11 °C. When the content of g-GO is 1.0 vol%, the bulk conductivity of PET/g-GO nanocomposite is increased by 8 orders of magnitude. However, when the content of GO is 1.0 vol%, the bulk conductivity of the PET/GO nanocomposite is only improved by 3 orders of magnitude. PET/g-GO nanocomposites exhibit good antistatic properties. The PET/g-GO nanocomposite's conductive percolation threshold is 0.61 vol%, while that of the PET/GO nanocomposite is 1.64 vol%. The electrical conductivity of the nanocomposite increases with the increase of graphene content. And the well-dispersed modified graphene can improve the electrical conductivity of the nanocomposite.